2017
DOI: 10.1038/s41598-017-03191-0
|View full text |Cite
|
Sign up to set email alerts
|

Human uterine lymphocytes acquire a more experienced and tolerogenic phenotype during pregnancy

Abstract: Pregnancy requires a delicate immune balance that nurtures the allogeneic fetus, while maintaining reactivity against pathogens. Despite increasing knowledge, data is lacking on the transition of pre-pregnancy endometrial lymphocytes to a pregnancy state. Here, we immunophenotyped lymphocytes from endometrium (MMC), term decidua parietalis (DPMC), and PBMC for direct comparison. We found that the immune cell composition of MMC and DPMC clearly differ from each other, with less NK-cells, and more NKT-cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
57
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 53 publications
11
57
5
Order By: Relevance
“…Depletion of Tregs leads to pregnancy failure and autogenic Tregs transfusion into the uterus protects from fetal loss in abortion‐prone mice . Congruously, a higher number and percentage of tolerogenic CD4 + CD25 high Tregs has been detected in peripheral blood and term decidua parietalis of early pregnant women than that of non‐pregnant women, indicating that gestation promotes Treg expansion . Of note, the proportion of Tregs in the peripheral blood and the decidua is reduced in unexplained miscarriages .…”
Section: T Regulatory Cellsmentioning
confidence: 99%
“…Depletion of Tregs leads to pregnancy failure and autogenic Tregs transfusion into the uterus protects from fetal loss in abortion‐prone mice . Congruously, a higher number and percentage of tolerogenic CD4 + CD25 high Tregs has been detected in peripheral blood and term decidua parietalis of early pregnant women than that of non‐pregnant women, indicating that gestation promotes Treg expansion . Of note, the proportion of Tregs in the peripheral blood and the decidua is reduced in unexplained miscarriages .…”
Section: T Regulatory Cellsmentioning
confidence: 99%
“…Uterine cell profiling of the murine estrous cycle showed that B cells constituted 1.5% of viable cells at estrus (12). In humans, B cells are considered rare lymphocyte subpopulations in the uterus with a median of 2% in pre-implantation uterine tissue and 5% in the decidua (13,14). Moreover, the functional promiscuity of B cells also poses an added layer of complexity in describing the specific role of B cells in pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the immunoglobulin levels of IgM, IgA, and IgG in the peripheral circulation are also increased in murine pregnancy in comparison to non-pregnant mice (129). Studies in humans reported that absolute counts of B cell peripheral compartment in the last trimester of pregnancy and in term decidua are decreased in comparison to non-pregnant controls (130,131). HELLP is not typically described as an autoimmune disorder, however, it is highly prevalent in pregnant women with autoimmune diseases such as acute phospholipid syndrome, systemic lupus erythematosus and thrombotic thrombocytopenic purpura (132)(133)(134)(135).…”
Section: B Cells In Hellpmentioning
confidence: 98%